An extended natural excitation technique for the modal analysis of ambient power system data - Nuño-Ayón, Jose J. (2021)
Nowadays, various advanced signal processing techniques have been developed to analyze ambient power system data obtained from wide-area measurement systems. An extended natural excitation technique is proposed in this paper for characterizing the dynamic information contained in the ambient data. This novel technique is based on the natural excitation technique and parallel factor decomposition. The proposed technique uses the correlation of the measured data through several correlation matrices that are used to form a third-order tensor. From this correlation tensor, the impulse responses of the power system can be extracted by parallel factor decomposition. After, the eigensystem realization algorithm is applied to each impulse response to estimate its oscillatory frequency and damping ratio. The proposed technique is applied to ambient data obtained from transient stability simulations of the New England-New York power system. The results indicate that the oscillatory frequencies and damping ratios can be accurately estimated using the proposed technique. Therefore, it is concluded that the proposed technique could be used for monitoring the ambient oscillations using wide-area measurement systems.